Atypical Hemolytic Uremic Syndrome: A Nationwide Colombian Pediatric Series (2024)
Objectives. Atypical hemolytic uremic syndrome (aHUS) is a rare complement-mediated kidney disease with genetic predisposition and represents up to 10% of pediatric hemolytic uremic syndrome (HUS) cases. Few studies have evaluated aHUS in Latin American population. We studied a Colombian pediatric cohort to delineate disease presentation and outcomes. Methods. A multicenter cohort of 27 Colombian children with aHUS were included. Patients were grouped by age at onset. Clinical features were compared using analysis of variance (ANOVA) and Fisher exact tests. Renal biopsy was performed on 6 patients who were suspected of having other renal diseases before aHUS diagnosis. Results. Most patients were male (70%). The onset of aHUS occurred frequently before age 4 years (60%) and followed gastroenteritis as the main triggering event (52%). Age groups showed comparable clinical presentation, disease severity, treatment, and outcomes. Pulmonary involvement (67%) was the main extrarenal manifestation, particularly in the 1 to 7 age group (P = .01). Renal biopsies were as follows: 3 had membranoproliferative glomerulonephritis (MPGN) type I, one MPGN type III, one C3-glomerulonephritis, and one rapidly progressive GN. Genetic screening was available in 6 patients and identified 2xCFHR5, 2xMCP, 1xADAMTS13/ THBD, and 1xDGKE mutations. A total of 15 relapses were seen, of which 8 (72%) occurred in the 1 to 7 age group. The renal outcome was not significantly different regardless of age group. Conclusion. In our cohort, we observed a relatively high frequency of extrarenal involvement at first presentation represented by pulmonary manifestations. The renal prognosis at initial presentation was worse than in previous reports.